2014
DOI: 10.1186/2196-1115-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a research agenda for data science

Abstract: I describe a research agenda for data science based on a decade of research and operational work in data-intensive systems at NASA, the University of Southern California, and in the context of open source work at the Apache Software Foundation. My vision is predicated on understanding the architecture for grid computing; on flexible and automated approaches for selecting data movement technologies and on their use in data systems; on the recent emergence of cloud computing for processing and storage, and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This has been achieved by making progress on all four research tracks identified by Mattmann as critically important for future data science, based on many years of experience at NASA and at the Apache Software Foundation [36].…”
Section: Discussionmentioning
confidence: 99%
“…This has been achieved by making progress on all four research tracks identified by Mattmann as critically important for future data science, based on many years of experience at NASA and at the Apache Software Foundation [36].…”
Section: Discussionmentioning
confidence: 99%